(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic brought about major changes in the lifestyle of the world population. Due to the lack of vaccines or a definitive treatment for disease, governments around the world have adopted social isolation and quarantine as methods to control the spread of the virus. Objective: Thus, the objective of this study was to discuss how social isolation and quarantine periods affected people’s mental health and quality of life during the COVID-19 pandemic. Methods: An integrative literature review was carried out during the COVID-19 pandemic between March and September 2020, establishing the following guiding question: How did social isolation and quarantine affect the mental health and quality of life of the population in the COVID-19 pandemic? Results: The final sample consisted of nineteen (19) articles, two (2) addressed depression during the pandemic period, three (3) presented the pandemic and the relationship with sociodemographic aspects, five (5) analyzed mental health in the pandemic, four (4) reported the impact of COVID-19 on the population’s style and quality of life and the last five (5) demonstrated the quality of human relationships and emotional aspects in the face of the pandemic. Conclusion: It was demonstrated that isolation and the quarantine period had a negative impact on the population’s quality of life and long-term mental health.